Comparison of chikungunya virus culture propagated in two cell line; vero and C6/36 cell lines - Ridzwanurahim, bin Nazimudin (Universiti Malaysia Sarawak (UNIMAS), 2015)
Chikungunya is a mosquito-borne disease that has afflicted millions of people worldwide. Infection by the Chikungunya virus (CHIKV) causes symptoms including fever, rashes and arthralgia. The main aim of this study is to compare CHIKV propagated in two cell lines; Vero and C6/36 cell lines to identify the more conducive cell line for downstream assays. This was done by first culturing the cell lines before infecting the cell lines with the virus for viral replication. Cytopathic effects were observed in both cell lines, viral harvest titres were determined through viral plaque assay, and reverse-transcription polymerase chain reaction (RT-PCR) was conducted to confirm CHIKV along with viral RNA quantification. Findings suggest the C6/36 cell line to be the more conducive cell line.